EVALUASI LOKASI TERMINAL TIPE B MENJADI ALUN-ALUN KOTA (KOTA INDERALAYA KABUPATEN OGAN ILIR) - Carmo, F.D.; Siswanto, Arie; Yazid, M. (Jurusan Teknik Sipil dan Perencanaan Fakultas Teknik Universitas Sriwijaya, 2018)
The requirement of public open space has become a necessity of the urban community, as is the case of Inderalaya City where public open space has become a necessity too. Terminal Type B Inderalaya City is not functioning properly so that evaluated the location of the terminal and changed its function to the City Square. Where can be used as a place of social interaction activities for the community, sports activities, art and cultural activities, etc. This study examines how the functionality of type B terminal Inderalaya City and evaluate the terminal into the city square in fulfilling the needs of Public Open Space seen from the policy side taken. This research uses descriptive qualitative approach. Data analysis is done through field observation, literature study, open interview and documentation. The result of the research mentioned that Terminal Type B Indralaya City is not functioning properly. This can be seen from the aspects of facilities that are less well maintained, location aspect, terminal management aspect and so forth. Evaluation of terminal location is done by regulation and view existing condition of existing public open space, Type B Terminal can be utilized as Town Square.